To the admissibility of the civil law exemption of property from arrest, imposed in the criminal proceedings: domestic and foreign experience - N. Kashtanova (Правоприменение)
The subject of paper deals with the legal nature of measures of criminal procedural compulsionin the form of seizure of property.Methodological basis of the article is based on general scientific dialectical methods of cognitionof objective reality of the legal processes and phenomena that allowed us to conduct anobjective assessment of the state of legislation and law enforcement practice in the proceduralaspects of the cancellation of the seizure of property in criminal proceedings of Russia.The results and scope of it’s application. It is submitted that the cancellation of the seizureof the property (or the individual limit) is allowed only on the grounds and in the mannerprescribed by the criminal procedure law of the Russian Federation. However, the studyfound serious contradictions in the application of the relevant law. In particular, cases inwhich the question of exemption of property from arrest (exclusion from the inventory),imposed in the criminal case was resolved in a civil procedure that, in the opinion of theauthor of the publication, is extremely unacceptable.On the stated issues topics analyzes opinions of scientists who say that the dispute aboutthe release of impounded property may be allowed in civil proceedings, including pendingresolution of the criminal case on the merits. The author strongly disagrees with this positionand supports those experts who argue that the filing of a claim for exemption of propertyfrom arrest (exclusion from the inventory) the reviewed judicial act of imposing of arrestwithout recognition per se invalid. In this regard, the author cites the legal position ofthe constitutional Court of the Russian Federation, from which clearly follows that of theright of everyone to judicial protection does not imply the possibility of choice of the citizenat its discretion, techniques and procedures of judicial protection, since the features of suchjudicial protection is defined in specific Federal laws.The author analyzes and appreciates Kazakhstan's experience of legal regulation of the permissibilityof filing a civil claim for exemption of property from seizure imposed in criminalproceedings. The author notes that the new civil procedural legislation of the Republic ofKazakhstan, which came into force from 01 January 2016, clearly captures that considerationin the civil proceedings are not subject to claims for exemption of property from seizureby the criminal prosecution body.Conclusions. Necessity of amendment to article 422 of the Civil Procedure Code of Russia:this article should not apply to cases of application of measures of criminal procedural compulsionin the form of seizure of property. Among other things, the author proposed additionsto part 9 of article 115 of the Criminal Procedure Code of Russia.